Retrospective Comparison of Cefdinir, Cephalexin, and Sulfamethoxazole-Trimethoprim in the Treatment of Outpatient Pediatric Urinary Tract Infections. (January 2023) - Cardinale, Brianna; Zembles, Tracy N; Ray, Katie; Bushee, Glenn; Liegl, Melodee; Simpson, Pippa; Mitchell, Michelle
This retrospective single-center study included children aged 2 months to 18 years who were prescribed an oral antibiotic for microbiologically confirmed urinary tract infection (UTI). The primary outcomes were re-encounter to the hospital, emergency department, or urgent care within 30 days and modification of the antibiotic regimen within 14 days. Development of Clostridioides difficile ( C difficile ) infection or new allergic reaction to the antibiotic prescribed was the secondary outcome. The sample included 2685 children. Rates of re-encounter were similar regardless of the initial antibiotic prescribed ( P = .88), and patients who received cefdinir had a lower rate of medication changes (5%) compared with both cephalexin (14%) and sulfamethoxazole-trimethoprim (15%) ( P ≤ .001). The most common reason for medication change was susceptibility interpretation. Given its low side-effect profile and narrow spectrum compared with the alternatives, cephalexin appears to be a reasonable choice as first-line therapy for the treatment of uncomplicated pediatric UTI.